Investimentos em infraestrutura financiados pelo BNDES e seus impactos sobre o PIB per capita regional no período 2003-2014 - Machado, Matheus Samarone (2018)
The present research seeks to estimate, through a panel data model, the impacts of the infrastructure investments financed by the BNDES per capita on GDP per capita in each region of Brazil, in order to compare the results between the regions in the period 2003-2014. In order to analyze differences between their multipliers and their conditions after the investments, the impacts were estimated with a one-year gap and without any gap between investments in infrastructure and GDP per capita in the regions. In addition, this research also discusses investments in infrastructure in Brazil, its recent history, the role of BNDES in its promotion and its effects on economic growth